A Comparison of Staff Development Policies and Practices and Teachers’ Job Performance in Nigerian and Pakistani Universities - Adewale Awodiji, Omotayo; Y. S. Ijaiya, Nike; Ahmad, Mansoor (International Journal of African Higher Education, 2022)
A university’s ability to remain competitive in a knowledge-driven world depends on the development of its teaching staff. The government and the private sector have invested in staff development in Nigerian and Pakistani universities. This article compares their staff development policies and practices as well as teachers’ job performance. An expo-facto comparative research design was adopted. We found significant differences between universities’ staff development policies and practices as well as lecturers’ job performance in the two countries (F (3, 657) = 41.879, ρ =.000). The article recommends effective implementation of staff development policies (funding, selection, performance appraisal, and promotion) to enhance staff’s skills and competencies and improve Nigerian universities’ position in global rankings. Key words: Staff development, policies, practices, teachers, performance